Unions and New Office Technology - Gattiker, Urs; Paulson, Dan (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1999)
To explain white-collar workers' expectations about what unions should do when technological change occurs in the workplace, two attitude scales were used. The data indicate that the industries in which employees works as well as their perception about whether computerized technology makes their job rewarding or creates de-skilling are all significant predictors of their attitude regarding a union's decision to accept or resist technological change. Income, hierarchical level, industry, job task, whether the computerized technology makes the job interesting, and whether the computerized technology is required to perform the job are significant predictors of an employee's attitude regarding a union's function to assist an employee to adapt to technological change. Non-union members and managers, in contrast to union members, appear to be concerned primarily about (1) bread-and-butter issues (e.g., wages, benefits, job security) and (2) quality of work issues (e.g., skills, training, and safety) and, therefore, somewhat less likely to feel positive about a union that accepts and helps workers adapt to new office technology.